Pembatasan Asupan Cairan pada Pasien Penyakit Ginjal Kronik yang Menjalani Dialisis dan Non-Dialisis : Narative Review - Suandika, Made; Sari, Syalsa Bila; Aprilia, Isma; Soleha, Putri (Pustaka Galeri Mandiri, 2026)
Hemodialysis is a complex and long-term renal replacement therapy that requires strict adherence to multiple medical recommendations, including fluid restriction, medication adherence, dietary regulation, and scheduled therapy sessions. Non-adherence to the hemodialysis regimen can worsen clinical conditions and increase the risk of complications, morbidity, and mortality. Therefore, effective and sustainable intervention strategies are needed to improve adherence among hemodialysis patients. This narrative review aims to integrate recent findings from studies that examine various adherence-enhancing interventions, including interactive education, psychosocial support, behavioral interventions, and physiological monitoring. A narrative synthesis was conducted through a literature review of ten recent studies evaluating the effectiveness of different approaches, such as teach-back methods, nurse-led follow-up calls, behavioral self-regulation strategies, psychosocial support, and physiological monitoring, in improving adherence to fluid restriction and therapeutic regimens. The findings indicate that interactive educational interventions, particularly teach-back techniques and nurse follow-up calls, significantly improve patient understanding and adherence to treatment protocols. Behavioral interventions, including self-regulation and positive coping skills training, support patients’ psychological adaptation to long-term therapy. In addition, psychosocial support from family and healthcare professionals enhances motivation and promotes sustained adherence. Routine physiological monitoring, such as assessment of interdialytic weight gain, further supports adherence to prescribed regimens. Overall effectiveness